2008
DOI: 10.1016/j.nuclphysbps.2008.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon width and gluonic component of

Abstract: We analyse data on ππ and γγ scattering below 700 MeV within an improved analytic K-matrix model. This model is based on an effective theory with couplings between resonances, hadrons and photons. The two-photon decay of a resonance can proceed through intermediate transition into charged hadrons (here: π + π − ) and their subsequent annihilation or through a "direct" transition into photons. Our analysis confirms the rather large total radiative width of the σ resonance which we find as (3.9 ± 0.6) keV but su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 35 publications
17
76
0
Order By: Relevance
“…This means that Yang-Mills theory has a higher ground state than full QCD as quarks lower it to the pion mass. Indeed, f 0 (600) or σ seems to have a large gluonic content due to the very small width for γγ decay that can be due to ππ rescattering [29,30] and as also seen through χPT [31,32]. We have shown that our computed mass is very near the one obtained from experiments [33].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…This means that Yang-Mills theory has a higher ground state than full QCD as quarks lower it to the pion mass. Indeed, f 0 (600) or σ seems to have a large gluonic content due to the very small width for γγ decay that can be due to ππ rescattering [29,30] and as also seen through χPT [31,32]. We have shown that our computed mass is very near the one obtained from experiments [33].…”
supporting
confidence: 57%
“…A more conservative choice of 410 MeV can take both σ and σ * , the latter eventually being f 0 (980), to agree with measured data giving m σ ≈ 491 M eV and m σ * ≈ 982 M eV . This view is shared in recent analysis [29,30]. But while these resonances are seen both experimentally and theoretically and, in indirect way through lattice computations for the propagator, a direct evidence on lattice computations for spectra appears difficult to achieve presently [34].…”
mentioning
confidence: 99%
“…Eqs. (11,12). Indeed, there is probably no closer link between amplitudes with definite t-channel quantum numbers and their low energy behaviour in the schannel physics region than that shown here.…”
Section: Discussionmentioning
confidence: 61%
“…We introduce a real analytic form factor shape function [2]: It allows for an Alder zero s = s AP and a pole at σ DP < 0 to simulate left hand singularities. The unitary I = 0 S wave ππ scattering amplitude is then written as:…”
Section: Channel ⊕ "Bare" Resonancementioning
confidence: 99%
“…-This model is improved by introducing a form factor shape function in a single channel [2], which is generalized [3][4][5] to the coupled channels case in order to extract the pole postions and the previous couplings of the σ and f 0 (980). In this talk, we review these recent results.…”
Section: Introductionmentioning
confidence: 99%